Moisture and thermal degradation of Cyanate-Ester-Based Die Attach Material - Gonzales, John Ivan J. (Philippine Engineering Journal)
Cyanate ester based thermo setting die attach materials, commonly known as Low Temperature Die Attach (LTDA) are the newest innovation in Hermetic Die Attach Technology due to their improved manufacturability, high decomposition temperature and a moisture gettering effect. Although their dispensability and decomposition temperatures are well documented, little information is available on the effects of prolonged exposure to moisture and thermal conditions. A study was therefore conducted to investigate the behavior of LTDA under thermal and moisture conditioning. Results of the experiment showed that the LTDA initially exhibit weight loss and subsequent weight gain after prolonged exposure. Incorporation of the moisture into the polymeric structure was verified by Infrared Spectroscopy. Die shear strength was also observed to decrease exponentially with exposure time. The time to failure equation (10 kilograms die shear strength) as a function of temperature and humidity was established to follow the model. tr=(percent RH)n exp (E/kT), n<0 Calculations for shop floor condition (25 C/55 percent RH) show that an exposure time in the order of 106 hours is required for the die shear strength to degrade to 10 kilograms for a 224x225 mil die.